2007
DOI: 10.1007/s11695-007-9144-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Outcome Two Years after Restrictive Bariatric Surgery

Abstract: Parallel with a considerable weight loss after bariatric surgery, important aspects of mental health such as depressive symptoms and self-esteem improved significantly. These effects appear 1 year after surgery, but do not seem to change considerably afterwards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 42 publications
7
41
0
5
Order By: Relevance
“…In contrast, weight loss may bring significant improvements in physical function, self-esteem, sexual life, health-related quality of life and overall mental health status. 43,44 On the other hand, stress reactions and depression have been linked to visceral fat accumulation and abdominal obesity. 45,46 People with emotional disorders or depression are often more likely to be overeating or have a binge eating disorder [47][48][49] and less likely to engage in physical activity, 50,51 which may contribute to weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, weight loss may bring significant improvements in physical function, self-esteem, sexual life, health-related quality of life and overall mental health status. 43,44 On the other hand, stress reactions and depression have been linked to visceral fat accumulation and abdominal obesity. 45,46 People with emotional disorders or depression are often more likely to be overeating or have a binge eating disorder [47][48][49] and less likely to engage in physical activity, 50,51 which may contribute to weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…18,148 However, evidence for an effect of bariatric surgery on depression is limited. Several longitudinal studies have explored the relationship between bariatric surgery and depression, identifying significant reductions in depression 149 and depressive symptoms 150,151 following surgery. One study found a decrease in depression from 32.7% at baseline, to 16.5% at 6-12 months, and 14.3% at 2-3 years following surgery.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, other studies reveal no significant changes in anxiety measurements postoperatively 48,49,56 .…”
Section: Mood Disordersmentioning
confidence: 82%
“…The majority of studies have reported a decrease in depression and depressive symptoms after bariatric surgery 24,27,[48][49][50][51][52][53][54][55][56] . Women seem to show a more marked decline than men 57 .…”
Section: Mood Disordersmentioning
confidence: 99%